Guyana : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Guyana. (IMF Staff Country Reports; Country Report ;, 2022)
Following the pandemic-induced recession in 2020, economic growth recovered in 2021, with non-oil GDP growth reaching 4.6 percent, despite being negatively impacted by floods. Inflation increased markedly since 2021 owing to the floods and supply-side disruptions, as well as continually rising fuel and food prices. Oil production increased and will ramp up substantially over the medium term.